Book review Debates in Design and Technology Education (2nd Edition), Hardy, A. (ed) (2022) - Hellard, Alice (Design and Technology Education: An International Journal, 2023)
This second edition of Debates in Design and Technology Education is situated within the somewhat precarious position that design and technology currently (still) holds in schools in the UK, and we are reminded of this context at a number of points through the book. At the same time, as stated by Alison Hardy in the introduction, it is also an acknowledgement of the new generation of research emerging within the subject, and as such is presented in part as a renewal or reframing. Much has happened, politically, socially, environmentally and technologically, since the first edition of Debates was published in 2013, and this second edition is a clear reflection of the related developments, though also at times the lack of development, in design and technology education. This volume presents debates around the subject in three distinct sections: political and international debates, the nature and perceptions of the subject, and classroom teaching, which provide the framing for the review that follows.